Effects of Aromatherapy on Anxiety and Vital Signs of Myocardial Infarction Patients in Intensive Care Units - N, Mirbastegan; J, Ganjloo; M, Bakhshandeh Bavarsad; MH, Rakhshani (IIUM Medical Journal Malaysia, 2016)
Introduction: Patients with myocardial infarction (MI) who were admitted to CCU experience anxiety. Anxiety increases the risk of ischemia and worsens the prognosis of MI. The aim of this study was to determine the effects of inhaling lavender oil on anxiety levels and vital signs in MI patients. Methods: A randomized controlled trial was performed. Sixty patients with MI were randomly assigned to the intervention and control group. The intervention group inhaled the essential oil of Lavender for three days (20-30 min/day, 3times/day) using a non absorbent paper which was stained with three drops of lavender oil. In control group steriled water was used. Each patient was assessed before and after intervention for the following clinical parameters: anxiety by state-trait anxiety inventory (STAI) and vital sign by Vista monitoring. The data were analyzed using Chi-square, paired t-test and Analysis of Covariance. Results: Results showed statistically significant decrease in state and trait anxiety at the end of study from 60.26±9.29 to 41.56±7.57 (P<0.001) and 55.73±10.22 to 44.53±7.28 (P<0.001) respectively, but in the control group were observed statistically significant increase in state and trait anxiety (P<0.001). Also statistically significant decrease were observed in blood pressure at the end of the intervention (p<0.05). The values for state and trait anxiety and blood pressure decrease in the intervention group in comparison with the control group (P<0.001 and p<0.05, respectively). Conclusion: This study showed that inhalation of lavender oil can reduce state and trait anxiety level and blood pressure in patients with MI.